Facial Merkel cell carcinoma in a 92‐year‐old man: A case report - Zhiqiang Zhang; Weiwei Shi; Ruzhi Zhang (Clinical Case Reports)
Key Clinical Message Merkel cell carcinoma (MCC) is a rare and aggressive skin cancer that can be easily misdiagnosed in its early stages. Clinicians should maintain a high index of suspicion for rapidly growing skin lesions in elderly patients and promptly investigate with histopathology and immunohistochemistry. Treatment for MCC should be individualized, considering the patient's age, overall health, and quality of life. Close follow‐up is essential to detect recurrence or metastasis early.